Rubber as a Construction Material for Corrosion Protection : a Comprehensive Guide for Process Equipment Designers. - Chandrasekaran, V. C. (Wiley-Scrivener, 2010)
Despite the long history of rubber as a construction material, this book is a unique publication as it comprehensively looks at the material in respect to the anti-corrosion requirements of the multitude of industries where rubber is used, both on land and off shore. This guide documents how rubber reliably meets the threats of corrosion and contributes to the longevity of the equipment. Chapters on ebonite, natural, and synthetic rubbers, examine their relevant properties and chemical resistance. Several case studies are included demonstrating the preferential choice of rubber as construction.